Performance trends of a large air-cooled steam condenser during windy conditions - Louw, Francois G. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2011.